Natural Conservation Base on Management of Sacred Cultural Landscape of Catur Angga Batukaru Temple in Tabanan-Bali - I Nyoman Wardi (Bumi Lestari Journal of Environment, 2020)
The study aimed to discuss the characteristic and environmental wisdom of the sacred Cultural Landscape of Catur Angga Batukaru temples in the conservation of natural resources in the regency of Tabanan-Bali. To reveal the research problems, data collection was conducted through observation, in-depth interview, and document study. The collected data were analyzed by the descriptive-qualitative technique. The results showed the structure of cultural landscape of Catur Angga Batukaru Temple consists of five cultural heritages as single vortices (sacred cultural landscape). The Batukaru Temple as a center with two main segments as subordinates, on west side, consists of Muncaksari and Tambawaras Temple, and on east side, consists of Petali and Besi Kalung Temple. Each unit managed by local communities generally comes from the Bali Age people. The management consists of the pengempon’s group temple, the institution of traditional villages, and subak's in the surrounding. As a living monument (temple), functioned as a sacred place to invoke safety, agricultural fertility, health, peace, and political stability. Similarly, through myth, ritual, and emission values the sanctity of the magical-religious, its cultural landscape located in the upstream region indirectly contribute very important to the conservation of the natural environment. As well as, the ritual uniqueness and aesthetic architectural values and beauty of the natural environment are so potential to be developed as a tourist attraction. In the modern era, in environmental degradation, it's very important to improve the welfare of local communities and conserving the natural environment in the context of sustainable development in Tabanan-Bali.